2015
DOI: 10.1177/1557988315606966
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Among Men With Disabilities: The Role of Health Care Providers

Abstract: Men with disabilities experience higher rates of interpersonal violence (IPV) than either women or men without disabilities, yet research exploring this problem is limited. This retrospective descriptive study examines the clinical files of male survivors of IPV with disabilities who received services from the Secret Garden, a disability-specific nonresidential IPV program located in New York City. These data inform the role health care providers may fill in helping address IPV against men with disabilities. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
2
9
0
2
Order By: Relevance
“…Furthermore, the body of literature showed that only 15.8% of victims were referred for IPV assistance by HCWs. 28 The current study found a shortage of medical equipment, which is in line with research in Tanzania. 8 The current study findings also showed that there was no collaboration with external organizations to prevent IPV and that a gap existed in the medico-legal reporting system, match a study in Serbia, 21 in which there was a weak support network for screening IPV.…”
Section: Provider Related Barriers and Trainingsupporting
confidence: 89%
“…Furthermore, the body of literature showed that only 15.8% of victims were referred for IPV assistance by HCWs. 28 The current study found a shortage of medical equipment, which is in line with research in Tanzania. 8 The current study findings also showed that there was no collaboration with external organizations to prevent IPV and that a gap existed in the medico-legal reporting system, match a study in Serbia, 21 in which there was a weak support network for screening IPV.…”
Section: Provider Related Barriers and Trainingsupporting
confidence: 89%
“…The few existing studies on GBV among PWDs indicate that PWDs are at equal or greater risk of GBV compared to their peers without disabilities [5][6][7][8][9][10][11][12][13][14]. PWDs report multiple forms of violence during their lifetime, by multiple perpetrators and for longer periods, compared to people without disabilities [5].…”
Section: Gbv Among People With Disabilitiesmentioning
confidence: 99%
“…To-date there is scanty research on the prevalence and risk factors of GBV among people with disabilities (PWDs) [5][6][7][8]. Moreover, research evaluating services and interventions that address GBV among PWDs is almost inexistent [9]. This eminent lack of data concerning PWDs obscures the state of GBV in this population, deterring political commitment and comprehensive public health engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it has been argued that disability further adds to the power disparities and lack of access resources associated with traditional gender roles [ 58 ]. While there is a dearth of methodologically robust studies, it is clear that both gender and type of disability affect the prevalence of violence [ 11 , 58 , 59 ]. It is critical that strategies to prevent violence are developed taking into account these intersectionalities [ 11 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%